Segmentasi Pemilih Moderat dan Tradisional: Peta Elektoral PKS Provinsi Maluku 2024 - Muhtar; Mukhlis Fataruba; Rukoyah (Indo Publishing, 2025)
The General Elections Commission (KPU) recapitulation (March 19, 2024) placed PAN as the winner of the most votes in the Indonesian House of Representatives (DPR RI) from the Maluku electoral district (178,770), followed by PKS (146,716) and PDI-P (145,777). This study asks: which voter segment—moderate or traditional—supported PKS's achievements, and what are the implications for the 2024 regional elections. Based on the segmentation–targeting–positioning (STP) framework and the Indonesian voter behavior literature, we formalize two constructs: the moderate segment (response to issues–performance–accountability) and the traditional segment (social–religious networks, local figures, culturally valuable services). The explanatory sequential mixed method design (quantitative → qualitative) anchors the analysis on official KPU data, accompanied by a proposed Moderate Index (IM) and Traditional Index (IT) for mapping per sub-district/urban village. The results show that PKS's best performance occurs when value politics meets network politics: in the high IM corridor, differentiation is determined by concrete policy language and public accountability; in the high IT corridor, the rhythm of da'wah (preaching) and social gatherings, rooted figures (including women), and cultural service packages secure votes. The decline in provincial DPRD seats indicates inefficient vote conversion due to thin distribution and the lack of anchor figures in several traditional pockets. Practical implications: STP orchestration based on the IM-IT map, focusing on